Framing in Delta and Omicron Variant News in CNN Channel on Youtube.Com ( A Discourse Analysis ) - Jaka Santri; Ansor Putra; Arman (ELITE: Journal of English Language and Literature, 2022)
This study aims to analyze the form of news framing of the Delta and Omicronvariants of Covid-19 on the CNN channel on youtube.com based on theperspective theory of Discourse Analysis of Framing Analysis by Zhondang Pan& Gerald M. Kosicki. The data were analyzed by describing and interpreting thedata to answer the research questions of this research. The writer analyzed twonews videos from the CNN channel. The writer found that the Delta andOmicron variants of news framing from Covid-19 on the CNN channel have atendency to similar schemes between the two video news, it is prioritizingcertain aspects developed by journalists. CNN also shows facts, information,statements and opinions of experts, governments, scientists and related parties tosupport the aspects of the news. Everything is explained by the writer in detail inSyntactical Structure, Script Structure, Thematic Structure, and RhetoricalStructure.